(1→3)-β-D-glucan in patients with pulmonary aspergilloma. Issue 4 (1997) - Yuasa Yuasa, Kazumi Kazumi; Goto Goto, Hajime Hajime
Abstract : To elucidate the role of (1→3)-β-D-glucan in pulmonary aspergilloma, serum concentrations of (1→3)-β-D-glucan were measured repeatedly for as long as 10 months in eight patients. In four patients with inactive disease, concentrations of (1→3)-β-D-glucan were in the normal range.The concentrations of (1→3)-β-D-glucan increased in two patients, although the disease was inactive. This increase might show the earliest stage of the invasive process of the disease. In two other patients with active disease, (1→3)-β-D-glucan increased. Other parameters, such as galactomannan, immunodiffusion and a radio-allergosorbent test, as well as inflammatory m arkers such as C-reactive protein and the leukocyte count, did not show any consistent tendency in regard to the activity of the disease. Thus, a (1→3)-β-D-glucan assay may add valuable data for evaluating the disease activity and understanding the disease process of pulmonary aspergilloma.